2016
DOI: 10.1002/btpr.2339
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of clarithromycin and alginate lyase against helicobacter pylori biofilm

Abstract: It is now established that the gastric pathogen Helicobacter pylori has the ability to form biofilms in vitro as well as on the human gastric mucosa. The aim of this study is to evaluate the antimicrobial effects of Clarithromycin on H. pylori biofilm and to enhance the effects of this antibiotic by combining it with Alginate Lyase, an enzyme degrading the polysaccharides present in the extracellular polymeric matrix forming the biofilm. We evaluated the Clarithromycin minimum inhibition concentration (MIC) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Thus, these antibiotics may have less impact on biofilm cells. In fact, recent in vitro studies have shown that clarithromycin is 4- to 16-fold less effective on H. pylori biofilm cells than on planktonic ones ( 26 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these antibiotics may have less impact on biofilm cells. In fact, recent in vitro studies have shown that clarithromycin is 4- to 16-fold less effective on H. pylori biofilm cells than on planktonic ones ( 26 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms can form on abiotic and biotic surfaces, including mucosal surfaces and on indwelling medical devices [55]. Bacterial biofilms can form in vivo in human beings, resulting from infections associated with chronic conditions such as bacterial endocarditis, cystic fibrosis, human gastric mucosal lesions and struvite nephrolithiasis [57,58]. Biofilms along with resultant immune responses are responsible for the development of chronic recalcitrant slowly-healing wound conditions such as venous leg ulcers and diabetic foot ulcers and are acknowledged contributors to antibiotic resistance [59,60,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Bb and Hp can independently form biofilms both in vitro and in vivo [21,22,58,60,62,63]. The formation of biofilms in vitro enabled the establishment of antibiotic resistant Bb cultures [60,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, H. pylori can form biofilms in gastric mucosa, and biofilm formation might enhance its resistance to drugs and the host immune system [21][22][23][24]33]. In vitro experiments have shown that the resistance of H. pylori ATCC43629 biofilm cells to clarithromycin is approximately eight-fold greater than that of planktonic cells [34]. Additionally, biofilm formation increases H. pylori TK1402 generation rates of drug-resistance mutations and its resistance to metronidazole, clarithromycin, and amoxicillin in vitro [22,24,35].…”
Section: Colonization Mechanismsmentioning
confidence: 99%